Women's Engagement in STEM Fields in Bangladesh: Trends, Obstacles, and Strategies - Tabassum, Nishat (Jurnal Administrasi Publik (Public Administration Journal), 2025)
The involvement of women in the Science, Technology, Engineering, and Mathematics (STEM) fields in Bangladesh raises significant concerns, particularly in light of the country's remarkable advancements in education and economic development. The female population constitutes half of Bangladesh's demographic, making their increased participation in the STEM fields not just essential but a necessity for addressing labor market needs and preventing talent shortages. The involvement of women in the STEM field fosters social justice by providing them with opportunities for high-paying and stable careers, thereby diminishing gender disparities in both education and employment. This article aims to examine the current trends and obstacles affecting women's participation in the STEM field in Bangladesh, as well as to identify potential strategic interventions that could be implemented to address these issues. This article is based on secondary sources. Despite significant progress in women's rights and representation across various sectors, the participation of women in STEM fields continues to be alarmingly low, with only about 14% of women engaged in these areas. This article identifies several barriers faced by women in the STEM field in Bangladesh, including societal and cultural obstacles, a scarcity of female role models and mentors, the absence of gender-inclusive policies, and a hostile work environment, among others. This article proposes that there is a need to enhance the enrollment of women in STEM disciplines. Educational institutions must proactively engage in initiatives that foster STEM education, specifically for girls. Organizations must establish a supportive work environment to ensure the retention of female employees.